Changes in Motor Skills of Children who Train Sports Swimming at the Initial Stage of School Education (in an Annual Training Cycle) - Paweł Eider; Krzysztof Wilk; Michał Tarnowski; Robert Terczyński (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
This paper presents an empirical approach to the changes in motor skills of children who train sports swimming at the initial stage of school education in an annual training cycle. Swimming belongs to the disciplines in which training starts at the age of 6-7. The proper selection of candidates to train certain disciplines is a complex process as they should be chosen from a large population of children, both girls and boys, having specific somatic and motor characteristics which, developed in the long-term, will enable them to achieve sports mastery. The aim of the research was to define which changes in motor skills occur in girls who train sports Aim: swimming in an annual training cycle. The Subject group consisted of 85 girls aged 7 who attended four elementary schools in Szczecin, Poland. 36 of them belonged to the Swimmers group and they were all members of the Municipal Swimming Club (MKP) in Szczecin. The Control group consisted of 49 girls who attended the same elementary schools. All subjects took part in two examinations (carried out in the school year 2009/2010. Physical ability tests were conducted in gyms. Motor skills were assessed with EUROFIT Test Battery which is the most reliable and accurate tool according to scientific research. The research revealed changes in both groups (Sw, C) in terms of all eight tests. Examination II proved statistically significant improvement of results in both groups (Sw, C) in comparison to Examination I. Changes between Examination I and Examination II results were most visible in the Swimmers groups in terms of balance, agility, static strength, functional strength and agility run. Changes between Examination I and Examination II were similar in both groups (Sw, C) in terms of speed of limb movement, explosive strength and torso strength. Progressive changes in motor skill of subjects are a positive phenomenon in the physical development of a child. Swimming training resulted significantly in positive changes in terms of motor skills of subject who were at the initial stage of swimming trainings, compared to their non-training peers. Participation in organized, regular sports classes results in the development of motor (physical) skills of children.